Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Likuiditas, dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Buono Aji Santoso; Irawati Junaeni (Politeknik Ganesha Medan, 2022)
The firm value can be measured through several financial ratios. The success of the company’s performance can be seen from the firm value, the better the value of the company, the more interested investors will be to invest their shares in the company. The purpose of this study is to elaborate and analyze the effect of probability, leverage, firm size, liquidity and firm growth on firm value. The sampling technique used by the author is purposive sampling technique with sample of LQ45 companies listed on the Indonesia Stock Exchange for the period 2018-2020. In this study, the approach used is a quantitative approach with data analysis techniques using multiple linear regression analysis with the help of statistical software EViews 10. From the results of research conducted partially, only one variable, namely Profitability (ROE), has a positive effect on firm value. Simultaneously, the value of the company (PBV) is influenced by profitability (ROE), leverage (DER), firm size (SIZE), liquidity (Current Ratio), and company growth (GROWTH) of 98%.